Structural Vulnerability Assessment of Historical Buildings in Turkey - Kasim Korkmaz; Asuman Carhoglu (Salehan Institute of Higher Education, 2017)
Structural Vulnerability assessment of historical buildings is very important to carry them to the future. Turkey is a rich country in terms of historic masterships mostly from Ottoman Empire, such as mosques, bathhouses, churches and aqueducts. Especially mosques are the common historical structures in turkey. Therefore, in the present study, structural vulnerability assessment of historical mosques in Turkey was carried out. One of the existing ones is considered as a sample building and structural vulnerability assessment was carried out on this building. The sample building was selected as Konak Mosque located in Izmir, Turkey. The mosque was structurally investigated through advanced approaches. The mosque, constructed in 1755 by Ottoman at very central location close by the clock tower, is little one decorated with blue tiles. The mosque is also nearby a historical bazaar where the main historical business stream line is located. Konak Mosque is one of these new styles in that age. It can be named as a signature historical building representing Islamic minimalist oriented architecture with its unique octagonal plan. In the present study, the building was modelled by using the Finite Element Modelling (FEM) software, SAP2000. Time history analyses were carried out using 10 different ground motion data. Displacements, base shear and stress values were interpreted and the results were displayed graphically and discussed. For probabilistic seismic risk assessment, fragility analyses were also carried out and the fragility curve and surface were sketched for the mosque. Saddle point was determined on the fragility surface.